Research on the influence of talent ecosystem on firm innovation performance: Based on the mediating role of collaborative innovation - Zhang, Wen; Liu, Chao (Frontiers in Environmental Science, 2022)
This paper extends previous studies on the organizational innovation by analyzing the impact of talent ecosystem on firm innovation performance in innovative enterprises. In addition, the mediating effect of collaborative innovation on the relationship between talent ecosystem and firm innovation performance is analyzed. Grounded in the Resource -Based View (RBV) theory, this paper develops an integrative research model which analyzes those relations using structural equation modeling on a dataset of 176 innovative enterprises. Results suggest that talent competence, organizational environment and regional environment of talent ecosystem have a significant positive impact on collaborative innovation, and organizational environment has a stronger effect on collaborative innovation; talent ecosystem can influence innovation performance to different degrees through the mediating role of collaborative innovation (technology synergy and capability synergy); technology synergy in collaborative innovation positively affects innovation performance, while Technology synergy in collaborative innovation positively affects innovation performance, while capability synergy has no significant effect on innovation performance. The findings of the study provide new ideas for enterprises to improve talent ecosystem and enhance innovation performance.